The effect of the community midwifery model on maternal and newborn health service utilization and outcomes in Busia County of Kenya: a quasi-experimental study - Duncan N. Shikuku; Geofrey Tanui; Mercy Wabomba; Dennis Wanjala; Josephine Friday; Taphroze Peru; Evelyne Atamba; Kenneth Sisimwo (BMC, 2020)
Abstract Background Poor women in hard-to-reach areas are least likely to receive healthcare and thus carry the burden of maternal and perinatal mortality from complications of childbirth. This study evaluated the effect of an enhanced community midwifery model on skilled attendance during pregnancy/childbirth as well as on maternal and perinatal outcomes against the backdrop of protracted healthcare workers' strikes in rural Kenya. Methods The study used a quasi-experimental (one-group pretest-posttest) design. The study spanned three time periods: December 2016-February 2017 when doctors were on strike (P1), March-May 2017 when no healthcare providers were on strike (P2), and June-October 2017 when nurses/midwives were on strike (P3), which was also the period when the project enhanced the capacity of community midwives (CMs) to provide services at the community level. Analysis entailed comparison of frequencies/means of maternal and newborn health service utilization data across the three periods. Results The monthly average number of clients obtaining services from CMs across the three time periods was: first antenatal care (ANC) (P1-1.8, P2-2.3, P3-9.9), fourth ANC (P1-1.4, P2-1.0, P3-7.1), skilled birth (P1-1.5, P2-1.7, P3-13.1) and the differences in means were statistically significant (p < 0.05). Over the period, the monthly average number of clients obtaining services from health facilities was: first ANC (P1-55.7, P2-70.8, P3-4.0), fourth ANC (P1-29.6, P2-38.1, P3-1.2) and skilled birth (P1-63.1, P2-87.4, P3-5.6), p < 0.05. There were no statistically significant differences in the average number of clients obtaining services from CMs or health facilities between P1 and P2 (p > 0.05). There was, however, a statistically significant increase in the average number of clients obtaining services from CMs in P3 accompanied by a statistically significant decline in the average number of clients obtaining services from health facilities (p < 0.05). First ANC increased by 68%, fourth ANC by 75%, skilled births by 68%, and postnatal care by 33% in P3 (p < 0.0001). There was a non-significant decline in macerated stillbirths and neonatal deaths in P3. Conclusions The findings underscore the importance of integrating community-level health service providers (CMs and health volunteers) into the primary health care system to complement service delivery according to their level of expertise, especially in low-resource settings.